Thực trạng quản lí hoạt động giáo dục kĩ năng sống cho trẻ mẫu giáo trong các trường mầm non thị xã Sơn Tây, thành phố Hà Nội theo hướng xây dựng “Trường học hạnh phúc” - Văn, Thị Nguyên (Tạp chí Giáo dục, 2024)
Life skills education is currently one of the top key tasks in preschools, especially for kindergarten children. However, managing this educational activity still has many difficulties and challenges. This study surveyed 85 people (83 managers and teachers in 6 preschools, 2 officials of the town's Department of Education and Training) to learn about the current status of managing life skills education activities for kindergarten children in preschools in Son Tay town and Hanoi city towards building happy schools, through 4 management functions including: planning, organizing, directing and controlling, and evaluating. Research results show that basically all functions are at a good level, but there are still uneven criteria in each function. The above results will be an important basis to help educational managers develop measures to improve the quality of these activities in accordance with the goals of preschool education in the direction of building happy schools.